(untitled) (Medical Forum Monthly, 2024)
Objective: to isolate Acinetobacter species and to evaluate its antibiotic susceptibility pattern in all types of clinical specimens of critically ill patients of Jinnah Hospital, Lahore. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Pathology Department, Allama Iqbal Medical College, Lahore from 1stJuly 2015 to 31st December 2015. Materials and Methods: One hundred clinical specimens obtained from the critically ill patients admitted in Jinnah Hospital, Lahore, were cultured using standard microbiological techniques and antimicrobial susceptibility pattern was evaluated using modified Kirby Bauer disc diffusion method following CLSI guidelines 2015. Results: The isolation rate of Acinetobacter baumannii was high as compared to the other species.Most of them were identified from the blood samples followed by the tracheal secretions and pus samples. The isolation rate of overall Acinetobacter species was high in ICU's and surgical wards. Antimicrobial susceptibility pattern revealed resistance rate of Acinetobacter species as co-trimoxasole 96(96%), gentamicin 82(82%)and ciprofloxacin 84(84%).Almost all of the isolates were susceptible to tigecycline and colistin. Conclusion: Acinetobacter species were resistant to most of the commonly used antibiotics. Only tigecycline has good susceptibility i.e 72% and colistin 100% susceptible to the Acinetobacter isolates from intensive care units.